Spontaneous complete necrosis of hepatocellular carcinoma caused by feeding vessel occlusion outside the tumour capsule - Tanaka, Hiroshi; Saeki, Satomi; Hiramatsu, Kiyoshi; Amemiya, Takeshi; Goto, Hidenari; Seki, Takashi; Arai, Toshiyuki (Indian Journal of Case Reports, 2017)
A 64-year-old man began treatment for chronic hepatitis C with peg-interferon and ribavirin. His hepatitis C virus ribonucleic acid (HCV-RNA) results turned negative. Just after the treatment, a computed tomography (CT) scan revealed a hypovascular mass in the segment 8. We performed a right hemihepatectomy as HCC. Upon macroscopic examination, the tumour was yellow and firm with a fibrous capsule. A wedge-shaped necrotic area was located at the top of an artery and a portal vein of segment 8. Necrosis was observed not only in the tumour but in the adjacent parenchyma. A histopathological examination showed that the tumour had been completely replaced by necrosis. This tumour was surrounded by capillary vessels and fed by several thick arteries, but organized thrombi were not detected. No viable cells were found. The histopathological diagnosis was a spontaneous complete necrosis of HCC caused by the occlusion of feeding vessels outside the capsule.